2018
DOI: 10.1002/mabi.201800132
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Ion Plasma Modification of Poly(Vinyl‐Alcohol) Increases Primary Endothelial Cell Affinity and Reduces Thrombogenicity

Abstract: Bulk material properties and luminal surface interaction with blood determine the clinical viability of vascular grafts, and reducing intimal hyperplasia is necessary to improve their long-term patency. Here, the authors report that the surface of a biocompatible hydrogel material, poly(vinyl alcohol) (PVA) can be altered by exposing it to reactive ion plasma (RIP) in order to increase primary endothelial cell attachment. The power and the carrier gas of the RIP treatment are varied and the resultant surface n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 36 publications
4
24
0
Order By: Relevance
“…In the whole blood ex vivo model without antiplatelet drugs, the plain PVA trended to the lowest platelet accumulation, supporting previous work that PVA has potential as a nonthrombogenic cardiovascular biomaterial. [14,33] An increase in platelet adhesion was seen for GFPGER-modified PVA compared to ePTFE, yet ePTFE had significantly more fibrin deposition when no antiplatelet drugs were used. To study the translatability of PVA with the endothelialization-promoting GFPGER modification, we tested the thrombogenicity of this material using clinically relevant antiplatelet therapies: ASA or DAPT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the whole blood ex vivo model without antiplatelet drugs, the plain PVA trended to the lowest platelet accumulation, supporting previous work that PVA has potential as a nonthrombogenic cardiovascular biomaterial. [14,33] An increase in platelet adhesion was seen for GFPGER-modified PVA compared to ePTFE, yet ePTFE had significantly more fibrin deposition when no antiplatelet drugs were used. To study the translatability of PVA with the endothelialization-promoting GFPGER modification, we tested the thrombogenicity of this material using clinically relevant antiplatelet therapies: ASA or DAPT.…”
Section: Discussionmentioning
confidence: 99%
“…After 48hrs of cell incubation, samples were stained using standard immunofluorescence procedures, as described previously. [33] Briefly, films were fixed and stained with Alexa Fluor ® 568 phalloidin, a primary VE-Cadherin antibody and secondary IgG1 Alexa-488, and DAPI. Films were mounted onto glass slides and imaged with a Nikon Ellipse TE-200U fluorescent microscope.…”
Section: Fluorescent Stainingmentioning
confidence: 99%
“…Previous in vitro cell adhesion studies with plasma treated PVA films have shown to improve endothelial cell attachment on the PVA treated with N 2 /H 2 , N 2 , O 2 , or Ar plasma (Ino et al, 2013; Cutiongco et al, 2016a; Jurney et al, 2018). These cell adhesion studies were conducted in a short term (2–6 days), and the plasma treatments were performed on flat surfaces or on the external surface of a tube.…”
Section: Introductionmentioning
confidence: 97%
“…The exposure of these surfaces to ionized gas leads to incorporation of chemical species, which results in surface functionalization. For example, it was previously reported that the wettability of plasma treated surfaces improves after the treatment to favor either bonding of coating material or cell adhesion (Nakagawa et al, 2006; Jacobs et al, 2012; Ino et al, 2013; Liu et al, 2014; Cutiongco et al, 2016a; Recek et al, 2016; Jurney et al, 2018). Depending on the gas type and the material that is interacting with the plasma, one can introduce different surface functional groups on the biomaterial surface.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has used a whole blood, ex vivo shunt model for many decades to evaluate the hemocompatibility of cardiovascular biomaterials [8][9][10][11][12][13]. The ability to control flow rate and local or systemic drugs makes the ex vivo whole blood shunt model very powerful for potential clinical translation.…”
Section: Introductionmentioning
confidence: 99%